Electronic Cigarette Use and the Risk of Cardiovascular Diseases - Espinoza-Derout, Jorge; Shao, Xuesi M.; Lao, Candice J.; Hasan, Kamrul M.; Rivera, Juan Carlos; Jordan, Maria C.; Echeverria, Valentina; Roos, Kenneth P.; Sinha-Hikim, Amiya P.; Friedman, Theodore C. (Frontiers in Cardiovascular Medicine, 2022)
Electronic cigarettes or e-cigarettes are the most frequently used tobacco product among adolescents. Despite the widespread use of e-cigarettes and the known detrimental cardiac consequences of nicotine, the effects of e-cigarettes on the cardiovascular system are not well-known. Several in vitro and in vivo studies delineating the mechanisms of the impact of e-cigarettes on the cardiovascular system have been published. These include mechanisms associated with nicotine or other components of the aerosol or thermal degradation products of e-cigarettes. The increased hyperlipidemia, sympathetic dominance, endothelial dysfunction, DNA damage, and macrophage activation are prominent effects of e-cigarettes. Additionally, oxidative stress and inflammation are unifying mechanisms at many levels of the cardiovascular impairment induced by e-cigarette exposure. This review outlines the contribution of e-cigarettes in the development of cardiovascular diseases and their molecular underpinnings.